Orchestration of chemomobilization and G-CSF administration for successful hematopoietic stem cell collection - Kriegsmann, Katharina; Schmitt, Anita; Kriegsmann, Mark; Bruckner, Thomas; Anyanwu, Adamma; Witzens-Harig, Mathias; Müller-Tidow, Carsten; Klein, Stefan; Wuchter, Patrick (Biology of blood and marrow transplantation, 2018)
Successful collection of peripheral blood stem cells (PBSCs) depends on the optimal orchestration of mobilization chemotherapy, granulocyte colony stimulating factor (G-CSF) application, and CD34+ cell number assessment in the peripheral blood (PB). However, determining the optimal timing in accordance to the applied chemomobilization regimen can be challenging. Although most centers apply their own local timing schedules, a reliable timetable including the currently most often used mobilization regimens is lacking. We present a comprehensive analysis of the timing modalities for 11 of the most commonly used chemomobilization regimens. A retrospective analysis was performed on the clinical and PBSC collection parameters (including duration of G-CSF application, time point of CD34+ assessment, PB CD34+ cell count, number of leukapheresis [LP] sessions, processed blood volume, and CD34+ collection results) of 91 representatively selected patients who had undergone stem cell mobilization at 2 collection centers. Six to 10 patients were analyzed per regimen with a variety of diagnoses, including multiple myeloma, malignant lymphoma, and sarcoma. No collection failures (<2 × 106 CD34+ cells/kg body weight) were observed. All analyzed patients successfully reached their individual collection goal in adherence to the given schedule of chemotherapy, application of G-CSF, measurement of CD34+ cells, and subsequent LP. The presented data on the timing of chemomobilization, G-CSF application, and stem cell collection may be helpful in clinical decision making and contribute to a more transparent and predictable treatment process.
Gesehen am 29.10.2019